Contemporary Second Economy and Business Contestations in South Africa - Makgamatha, M. G.; Meso, K. K. (International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa, 2018)
South Africa has countless entrepreneurs who engage in micro-enterprises that are ubiquitous in townships and rural areas. Accordingly, the current global landscape has given room to the proliferation of mushrooming informal businesses which are owned by competitive foreign nationals. A large majority of foreign nationals migrate to South Africa with capital, innovative ideas and skills to establish micro-enterprises; therefore, their businesses become more competitive than local traders. The informal economy in South Africa has given room for foreign entrepreneurs to establish and own factors of production including land. This paper posits that social capital, kinship and relations of reciprocity amongst competitive foreign national seems to be the common theme which sustains and more often than not proliferates informal businesses around poor third world township and rural areas in the second economy of South Africa. Unlike local informal traders who have been alienated from the mainstream production process through indoctrination of the "work for boss" mentality and unavailability of capital and skills; foreign traders seem to be spontaneously taking the upper hand. Thus, policy making efforts in the SMMEs sector have not offered a unique response in ensuring equitable distribution of productive opportunities amongst participants of the second economy, particularly indigent traders. South Africa’s spatial inequality, social fragmentation and regimes that pay continued reverence to qualification accumulation over sustainable job creation are largely responsible for the current trajectory in the informal economic landscape. It is against this background that this paper contributes, that the paucity of social capital, entrepreneurial skills, financial literacy and economic resilience amidst destitute local traders creates an inexorable cycle of income poverty and dependency. It concludes that a strong point of departure would be investment in an entrepreneurial centred curriculum coupled with industry specific skills and resource development for local informal traders.
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Entrepreneurship; Informal Trading; Social Capital; Entrepreneurship